Analysis of Step Up Transformer for Pulsed Electric Fields Generator - Yoppy Yoppy; Mohamad Khoirul Anam; Yudhistira Yudhistira; Priyo Wibowo; Harry Arjadi; Hutomo Wahyu Nugroho; Haryo Dwi Prananto (Institute of Advanced Engineering and Science, 2016)
Pulsed electric fields (PEF) is a novel non-thermal food processing whose purpose is inactivating microbes while at the same time preserving food’s nutrition, color, and taste. This paper presents an analysis of step up transormer for PEF high voltage generator. To achieve the optimum PEF effects, the pulse shape should resemble a square, which is characterized by low voltage drop and fast rising time. Through simulations, it has been shown that higher transformer inductance results in lower voltage drop. However at some points, further increasing the inductance would only produces negligible improvements. Meanwhile fast rising time can be achieved by minimizing leakage inductance and parasitic capacitance. Moreover, maximum energy transfer to the load can be obtained by reducing winding resistances. Finally, a case of high voltage generator using ignition coil has been evaluated. Due to its high winding resistances, ignition coil seems to be not suitable for PEF applications.